Foraging Behaviours of Breeding Arctic Terns Sterna paradisaea and the Impact of Local Weather and Fisheries - Morten, Joanne M.; Burgos, Julian M.; Collins, Lee; Maxwell, Sara M.; Morin, Eliza-Jane; Parr, Nicole; Thurston, William; Vigfúsdóttir, Freydís; Witt, Matthew J.; Hawkes, Lucy A. (Frontiers in Marine Science, 2022)
During the breeding season, seabirds are central place foragers and in order to successfully rear chicks they must adjust their foraging behaviours to compensate for extrinsic factors. When foraging, arctic terns Sterna paradisaea are restricted to the first 50 cm of the water column and can only carry a few prey items back to their nests at once. In Iceland, where 20–30% of the global population breed, poor fledging success has been linked to low food availability. Using GPS loggers, we investigated individual foraging behaviours of breeding adults during incubation from a large colony over four seasons. First, we tested whether foraging trip distance or duration was linked to morphology or sex. Second, we examined how trips vary with weather and overlap with commercial fisheries. Our findings reveal that arctic terns travel far greater distances during foraging trips than previously recorded (approximately 7.3 times further), and they forage around the clock. There was inter-annual variability in the foraging locations that birds used, but no relationship between size or sex differences and the distances travelled. We detected no relationship between arctic tern foraging flights and local prevailing winds, and tern heading and speed were unrelated to local wind patterns. We identified key arctic tern foraging areas and found little spatial or temporal overlap with fishing pelagic vessels, but larger home ranges corresponded with years with lower net primary productivity levels. This suggests that whilst changing polar weather conditions may not pose a threat to arctic terns at present, nor might local competition with commercial fisheries for prey, they may be failing to forage in productive areas, or may be affected by synergistic climatic effects on prey abundance and quality. Shifts in pelagic prey distributions as a result of increasing water temperatures and salinities will impact marine top predators in this region, so continued monitoring of sentinel species such as arctic terns is vital.